Length of hydraulic jump using artificial neural network - Boon, C.W (University Malaysia Sarawak (UNIMAS), 2004)
A relatively new tool, artificial neural network (ANN), was applied to simulate the relative length of hydraulic jump of the Natural stiling basin with horizontal floor (Basin 1). A set of data which was obtain from previous research were used as the input and target to train the neural networks.